'Magnetic illusion' can create magnetic fields at a distance. (March 2021) - Allen, Michael
Abstract : Physicists in the UK and Spain claim to have found a way to generate and manipulate magnetic fields at a distance, opening the possibility of projecting magnetic fields into inaccessible spaces and the remote cancellation of magnetic sources.